Interleukin-1 is responsible for acute lung immunopathology but increases survival of respiratory influenza virus infection. - Schmitz, N; Kurrer, M; Bachmann, M; Kopf, M (2005)
Interleukin-1alpha (IL-1alpha) and IL-1beta are proinflammatory cytokines, which induce a plethora of genes and activities by binding to the type 1 IL-1 receptor (IL-1R1). We have investigated the role of IL-1 during pulmonary antiviral immune responses in IL-1R1(-/-) mice infected with influenza virus. IL-1R1(-/-) mice showed markedly reduced inflammatory pathology in the lung, primarily due to impaired neutrophil recruitment. Activation of CD4(+) T cells in secondary lymphoid organs and subsequent migration to the lung were impaired in the absence of IL-1R1. In contrast, activation of virus-specific cytotoxic T lymphocytes and killing of virus-infected cells in the lung were intact. Influenza virus-specific immunoglobulin G (IgG) and IgA antibody responses were intact, while the IgM response was markedly reduced in both serum and mucosal sites in IL-1R1(-/-) mice. We found significantly increased mortality in the absence of IL-1R1; however, lung viral titers were only moderately increased. Our results demonstrate that IL-1alpha/beta mediate acute pulmonary inflammatory pathology while enhancing survival during influenza virus infection. IL-1alpha/beta appear not to influence killing of virus-infected cells but to enhance IgM antibody responses and recruitment of CD4(+) T cells to the site of infection.